Effect of NPK and plant extracted pyroligneous acid on yield of Boro rice - Masum, SM; Ali, MH; Chowdhury, IF; Mandal, MSH; Haque, MN (Bangladesh Agronomy Journal, 2015)
Abstract not available Bangladesh Agron. J. 2014, 17(2): 95-97